Kinda like brothers - Booth, Coe (New York : Scholastic Press, 2014)
When his mother takes in a twelve-year-old foster boy, Jarrett is forced to share his room and his friends with the new boy.
Keywords: Foster home care -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; African Americans -- Juvenile fiction; Foster home care -- Fiction; Interpersonal relations -- Fiction; African Americans -- Fiction